More than coffee – a World Café to explore enablers of pharmacy practice research. (27th April 2020) - Kavanagh, Oisín N.; Moriarty, Frank; Bradley, Catriona; O'Hagan, James; Stack, Gary; Kelly, Dervla
Abstract: Background: Pharmacists are in demand now more than ever to provide high‐quality expertise about the effectiveness, safety and use of medications. Amidst an increasingly complex and costly healthcare system, policy makers need robust evidence to justify public spending on pharmacy services. Research on the impact of existing and emerging pharmacy practices is required. Objective: To explore barriers and opportunities to enhance research among pharmacists in Ireland utilising a World Café methodology. Methods: A pharmacy research discussion day was held in November 2018, open to all pharmacists in Ireland. A World Café methodology was utilised as a mechanism to facilitate group discussions about pharmacy practice research. Results: Discussions with 63 attendees identified four themes and seventeen subthemes. The four themes were challenges undertaking research, research motivations, leadership and training. Subthemes included robust evidence, clinical, economic and societal outcomes, alignment with national and international health system priorities, need for incentives from professional training bodies, competitive business model and embed within schools of pharmacy. Conclusions: The most commonly discussed barriers inhibiting research were workload, technology limitations and financial considerations. Organisational leadership to prioritise and coordinate research efforts, training to build research capacity, building on existing examples of excellence and initiation of bottom‐up community‐based research projects were identified in our study as opportunities to enhance pharmacist involvement in research and ultimately patient health outcomes.